2020
DOI: 10.34069/ai/2020.27.03.11
|View full text |Cite
|
Sign up to set email alerts
|

International Migration & Economic Development: The Case of EU Countries

Abstract: The globalization of the modern world strengthens the role of migration flows in the socio-economic development of countries and regions. The European Union, and Italy in particular, are among the main centers attracting migrants due to their geopolitical transit position and relatively favorable environment. The consequences of the explosive growth in migration flows are ambiguous. To clarify the direction and power of such effects, we perform correlation and regression analysis according to a number of param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Finally, dyadic factors are characteristic of country pairs, and the determinant underlying this factor is generally geographic (Abel et al, 2019;Larotta Silva, 2019). The economic factors include unemployment (Harding & Neamţu, 2018;Kilic et al, 2019;Basile et al, 2019), income level (Nguyen, 2020;Laskienė et al, 2020;Slettebak, 2021), economic growth and development (Tolmacheva, 2020;Lyulyov et al, 2021;Rennó Santos et al, 2022), poverty (Kluge et al, 2019;Nowak-Lehmann et al, 2021;Diallo, 2022), the tax system (Lamantia & Pezzino, 2018;Guerreiro et al, 2020;Dai & Tian, 2021), economic freedom (Aarhus & Jakobsen, 2019;Gignarta et al, 2020;Arif et al, 2020). So, we can state that considering the main migration factors, it is evident that people leave their countries of origin to find better living conditions in foreign countries and to escape unfavourable environments.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, dyadic factors are characteristic of country pairs, and the determinant underlying this factor is generally geographic (Abel et al, 2019;Larotta Silva, 2019). The economic factors include unemployment (Harding & Neamţu, 2018;Kilic et al, 2019;Basile et al, 2019), income level (Nguyen, 2020;Laskienė et al, 2020;Slettebak, 2021), economic growth and development (Tolmacheva, 2020;Lyulyov et al, 2021;Rennó Santos et al, 2022), poverty (Kluge et al, 2019;Nowak-Lehmann et al, 2021;Diallo, 2022), the tax system (Lamantia & Pezzino, 2018;Guerreiro et al, 2020;Dai & Tian, 2021), economic freedom (Aarhus & Jakobsen, 2019;Gignarta et al, 2020;Arif et al, 2020). So, we can state that considering the main migration factors, it is evident that people leave their countries of origin to find better living conditions in foreign countries and to escape unfavourable environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, another branch of literature distinguishes between pull and push factors leading to immigration and emigration in a given country (Mohamed & Abdul-Talib, 2020;Unguren et al, 2021;Garelli & Tazzioli, 2021;Piras, 2021;Khalid & Urbański, 2021). The push factors leading to high emigration rates from a country are mainly corruption (Matallah, 2020;Arif, 2022), unemployment (Baumann et al, 2015;Cimpoeru, 2020;Espinosa & Díaz-Emparanza, 2021), unstable political environment (Mourão et al, 2018;Agadjanian & Gorina, 2019;Žižka & Pelloneova, 2019;Grumstrup et al, 2021;Kang, 2021), military instability (Habchak & Dubis, 2019;Veebel, 2020), climate changes (Barassi et al, 2018;Schutte et al, 2021;Reichman, 2022), low wages and income (Fischer & Pfaffermayr, 2018;Delogu et al, 2018), low or negative economic growth (Tolmacheva, 2020;Lupak et al, 2022;Gavurová et al 2017). The pull factors leading to high immigration rates to a country are high wages and income (Laajimi & Le Gallo, 2022), low level of poverty (Hager, 2021;Urbański, 2022), high standard of living (Hager, 2021), high economic growth (Schwabe, 2021), immigration and integration policy (Beverelli, 2022), welfare (Cebolla-Boado & Miyar-Busto, 2020;Ferwerda & Gest, 2021), immigrant networks (Kaplan et al 2016;Kabir, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the view of Nam et al (2020), financial markets and the quality of accounting and auditing positively influenced direct investment flows in the national economy. Tolmacheva (2020) conducted an empirical research regarding the role of migration on the socio-economic development of countries and regions in the European Union. Results reported that the most important factors were employment, GDP growth rate and labor cost index.…”
Section: Brief Overview Regarding the Impact Of International Trade H...mentioning
confidence: 99%
“…Sakharuk et al (2019) prove that in order to protect the rights of labor migrants the State has to introduce the system of collecting and analyzing the statistical information; to improve the economic well-being of the employees; to conclude bilateral agreements with other countries in the indicated area. Tolmacheva (2020) investigates the substance of international migration and identifies the factors affecting the trends in economic dynamics as well as changes in migration flows. Hasenau (1991) and Vittin-Balima (2002) study ILO standards for migrant workers.…”
Section: Literature Reviewmentioning
confidence: 99%